Valoración del riesgo de desarrollar diabetes mellitus tipo 2 a través del Test de Findrisk en la población de la cabecera cantonal del cantón Celica. - Bermeo Jimbo, Cinthya Dalila (2017)
Diabetes mellitus is a chronic, degenerative and incurable but controllable disease, describing a metabolic disorder of multiple etiologies, characterized by chronic hyperglycemia and disorders in the metabolism of carbohydrates, fats and proteins, resulting from defects in secretion and / or action of insulin. Many studies indicate that it is possible to significantly reduce or delay the incidence of this disease through the detection and early intervention of modifiable factors in people at risk. The present study was carried out through a quantitative, descriptive, cross - sectional study whose objectives were: to determine the 10 - year risk to develop type 2 diabetes mellitus by means of the Findrisk test in the population of the cantonal head of the canton Celica, to know the main risk factors, to determine the age and gender with greater risk and the subsequent elaboration of a prevention proposal; applying the survey to 326 habitants, a sample taken at random, it is concluded that 48.16% presents a low risk of developing type 2 diabetes, followed by a 34.97% slightly higher risk, in relation to gender, women presented higher risk and in relation the oldest age group was confirmed to be at greater risk, the main risk factors found in a decreasing manner were: overweight 44.17%, abdominal perimeter 39.8%, non-physical activity 38.04%, and minor percentage of non-consumption of fruits and vegetables and family history of diabetes. KEY WORDS: Findrisk test, risk factor and diabetes